BRAF and MEK inhibition beyond dabrafenib–trametinib in advanced thyroid cancer: a real-world case series - Yamin, Tzahi; Cohen, Oded; Robenshtok, Eyal; Izkhakov, Elena; Miodovnik, Mor; Gutfeld, Orit; Leshem, Yasmin; Meirovitz, Roman; Warshavsky, Anton; Muhanna, Nidal; Finkel, Inbar (Frontiers in Endocrinology, 2026)
ObjectiveBRAF V600E mutation is the most common and clinically significant genetic alteration in advanced thyroid cancers. This study provides real-world experience with BRAF and MEK inhibitors other than dabrafenib and trametinib in the treatment of advanced thyroid cancers harboring this mutation.MethodsA case series of four patients with advanced thyroid cancer (three papillary and one anaplastic) treated with various BRAF and MEK inhibitors. All patients had confirmed BRAF V600E mutation.ResultsAmong three patients treated with BRAF/MEK inhibitors for radioiodine refractory metastatic PTC, and one patient with ATC, all (100%) demonstrated a partial response (PR) during therapy, yielding an overall response rate (ORR) of 100%. Stable disease was observed in multiple treatment phases, contributing to a high overall disease control rate. Three patients had disease-related death, while one remained under treatment at last follow-up. The course of treatment was complicated by significant toxicities, leading to dose reductions or treatment discontinuations. Despite initial responses, all cases eventually progressed, necessitating sequential treatment strategies. Overall survival ranged from 6.0 to 25.3 months, with a median follow-up of 18.3 months since the initiation of BRAF and MEK inhibitors.ConclusionsThis case series highlights the potential benefits and challenges of targeted therapies in advanced thyroid cancer. While BRAF and MEK inhibitors offer new treatment options, toxicity management and the development of resistance remain significant hurdles. The limited FDA-approved options for BRAF V600E-positive thyroid cancer compared to melanoma underscore the need for further research to optimize and expand treatment strategies.